Development and validation of an LC-MS-based quantification assay for new therapeutic antibodies: application to a novel therapy against herpes simplex virus - Fresnais, Margaux; Longuespée, Rémi; Sauter, Max; Schaller, Torsten; Arndt, Michaela; Krauß, Jürgen; Blank, Antje; Haefeli, Walter E.; Burhenne, Jürgen (ACS omega, 2020)
Multiple therapeutic monoclonal antibodies (mAbs) are currently under development or in (pre)clinical study phases to reach regulatory approval. Among these, a new mAb against herpes simplex virus, HDIT101, was recently tested in healthy volunteers during a phase I clinical trial (first-in-human, dose escalation). In the frame of the pharmacokinetic evaluation of this new therapy, a mass spectrometric (MS)-based method was developed for the quantification of HDIT101 in human plasma using liquid chromatography coupled to tandem mass spectrometry. In this work, we describe the development of this bioanalytical assay using the quantification of a HDIT101 surrogate peptide, the assay validation procedure according to the FDA guidelines within the calibration range from 20 to 5000 μg/mL, and its application to plasma samples from the first-in-human clinical trial. This work presents a generic workflow for the development of MS-based quantification assays of new therapeutic antibodies that allows reaching high immunopurification recovery (>98% for HDIT101 over the full calibration range with a precision of 6.9% CV). Surrogate peptide and stable isotopically labeled internal standard were stable, and batch-to-batch accuracies and precisions at the four quality standard levels ranged between −2 and 5% bias and 8 and 11% CV, respectively.
Gesehen am 05.11.2020